2016
DOI: 10.1590/s1519-99402016000400007
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling a dry bakery by-product: effect of hydration using acid whey or water associated or not at urea

Abstract: SUMMARY The objective of this study was to investigate the characteristics of silages prepared with a dry bakery by-product hydrated with acid whey or water associated or not at urea. The trial was a 3 (hydration at three moisture levels: 250, 300, and 350 mL kg−1 of by-product) × 3 (three application rates of urea: 0, 5, and 10 g kg−1 of by-product) × 2 (liquid used at hydration: acid whey or water) factorial arrangement. Mini-silos were used as experimental silos and remained closed for 30 days. Overall, sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Aiming to use a bakery co-product waste, Rezende et al [75] tested possibilities of re-hydration, treating it with acid whey or water and levels of urea. The authors found that the resulting silages had reduced populations of molds and yeast by acidification process.…”
Section: Co-ensiling Forage With Food Processing Waste and Tmr Consermentioning
confidence: 99%
“…Aiming to use a bakery co-product waste, Rezende et al [75] tested possibilities of re-hydration, treating it with acid whey or water and levels of urea. The authors found that the resulting silages had reduced populations of molds and yeast by acidification process.…”
Section: Co-ensiling Forage With Food Processing Waste and Tmr Consermentioning
confidence: 99%
“…En esta investigación se observó que la fuente de carbohidratos fermentables aumentó (P<0.05) el efecto asociativo en las dietas de los tratamientos PO+MC (≥ 4.26%) y CF+MC (≥ 3.75%) con degradabilidad in vitro ≥ 829.71 g/kg MS; sin embargo, en los tratamientos con ensilados a base de SPP y en aquellos con UR este efecto fue negativo (Tabla 5). En el ensilaje de SPP con 300 o 350 mL/kg de agua con niveles crecientes de urea (5 y 10 g/kg), se observó efecto lineal sobre la concentración de ácido láctico (17.2 vs 23.6 g/kg MS), ácidos totales (22.9 vs 31.5 g/kg MS) y en el aumento de la concentración de ácido fítico (18.5 vs 22.6 g/kg MS), pero sin diferencias en el número de bacterias acido lácticas de 5.94 -5.81 log10 cfu -1 MS (Rezende et al, 2016). El aumento del ácido fítico por efecto de la inclusión > 30 g/kg MS urea en esta investigación, pudo expresarse en los ensilados a base de SPP y por lo tanto hizo indisponible el P de los carbohidratos.…”
Section: Tratamientosunclassified
“…Aiming to use a bakery co-product waste, Rezende et al (2016) tested possibilities of re-hydration, treating it with acid whey or water and levels of urea. The authors found that the resulting silages had reduced populations of molds and yeast by acidification process.…”
Section: Co-ensiling Forage With Food Processing Waste and Tmr Conservationmentioning
confidence: 99%